Five ways to make architecture political an introduction to the politics of design practice - Yaneva, Albena (Bloomsbury, 2017)
"Five Ways to Make Architecture Political presents an innovative pragmatist agenda that will inspire new thinking about the politics of design and architectural practice. Moving beyond conventional conversations about design and politics, the book shows how recent developments in political philosophy can transform our understanding of the role of designers. Introducing the framework of contemporary post-foundational politics in a way that is accessible to designers, it asks: how, when, and under what circumstances can design practice generate political relations? How can architectural design become more 'political'? Five central chapters, which can be read alone or in sequence, explore the answers to these questions. Powerfully pragmatic in approach, each presents one of the 'five ways to make architecture political', and each is illustrated by case studies from a range of contemporary situations around the world. We see how politics happens in architectural practice, learn how different design technologies have political effects, and follow how architects reach different publics, trigger reactions and affect different communities worldwide. Combining an accessible introduction to contemporary political concepts with a practical approach for a more political kind of practice, this book will stimulate debate among students and theorists alike, and inspire action in established and start-up practices"...
Includes bibliographical references
Keywords: ARCHITECTURE / General; ARCHITECTURE / Professional Practice; ARCHITECTURE / Criticism; Architektur; Politik; Architecture and society; Architecture -- Political aspects; Politische Ästhetik